Students. poor perceptions about school: challenge to school counsellors (2014)
"The purpose of the study was to examine secondary school students 'perception and the challenges it poses to guidance counselors in the school community. The participants for the study comprised 205secondary school students in Ido Local Government Area, Oyo State. Descriptive survey research design was employed. A simple random technique was employed in selecting 205 participants across the Local Government Area and four instruments were used to collect data. Their age ranged between 11 years 17years with the mean age of 10.4 years and the standard deviation 4.68. Pearson's Product Moment Correlation and Multiple regression analysis was used to analyze the data. The results showed that social support was the most potent factors contributing to students' perception about school. Parents, teachers ,guidance counselors as well as government should cooperate in changing students' perception about school so as to have a fulfilling stay in school. "